The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.746540
|View full text |Cite
|
Sign up to set email alerts
|

Asian “Guan” Parenting and Life Satisfaction Among Adolescents in Malaysia: The Mediating Role of Filial Piety

Abstract: Literature on adolescent development has shown that parenting practices have positive relationships with adolescents’ life satisfaction. Adolescents’ life satisfaction improves when they have parents low in psychological control who uphold reciprocal self-disclosure in their communication. Guan parenting was found to correlate positively with adolescents’ development. Therefore, it is methodologically important to replicate the investigation on the relationship between adolescents’ life satisfaction and Guan p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…These areas are also deeply influenced by Confucius culture. Empirical studies have demonstrated that filial piety belief has a significant impact on young people from East Asia ( Ismail et al, 2009 ; Nainee et al, 2022 ), suggesting that the present conclusion may be found in these countries.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These areas are also deeply influenced by Confucius culture. Empirical studies have demonstrated that filial piety belief has a significant impact on young people from East Asia ( Ismail et al, 2009 ; Nainee et al, 2022 ), suggesting that the present conclusion may be found in these countries.…”
Section: Discussionmentioning
confidence: 68%
“…Children’s perceived parental authority can reduce parent–child conflicts, thus decreasing delinquency; parental legitimacy mediates the effect of parenting style on changes in delinquency ( Zhang et al, 2006 ; Trinkner et al, 2012 ). Similarly, AFP significantly impacts on parent–child conflicts and children’s externalizing behaviors; AFP can act as a mediator on the association between parenting style and children’s life satisfaction ( Li et al, 2014 ; Nainee et al, 2022 ). Given these similarities, we speculate that children’s perceived legitimacy of parental authority may influence cyberbullying perpetration.…”
Section: Discussionmentioning
confidence: 99%
“…The results extend the cross-cultural validity of the DFPM to Eastern Europe, and provide a counterpoint to paradigm of East-West differences. Nainee et al (2021) also applied the Malaysian version of the DFPS to elucidate the relationships among parenting style, filial piety, and life satisfaction for adolescents in Malaysia as well. In addition, Lim et al (2022) applied the English version of the DFPS to Asian and Caucasian Americans to demonstrate the cross-cultural applicability of the DFPM on the topic of caring for elderly parents and the potential to reflect significant filial differences within an individualist society.…”
Section: Reflective Emic and Reflexive Etic Approaches To Constructin...mentioning
confidence: 99%
“…According to ecological system theory, parental factors, as important micro-system factors, may interact with individual factors (e.g., career exploration) in adolescent development (Bronfenbrenner, 1977). Although numerous studies have demonstrated the role of general parenting behavior in adolescent social development outcomes (e.g., LS, empathy, and cyberbullying) (Avci & Sak, 2018; Liang et al, 2021; Nainee et al, 2021; Wu et al, 2021; Zhang et al, 2021b), few studies have explored the role of specific parenting behaviors related to career development. “Career-specific parental behaviors refer to the concrete actions parents use to guide the career development of their children” (Dietrich & Kracke, 2009; Guan et al, 2015, p. 95).…”
Section: The Moderating Role Of Parental Career Supportmentioning
confidence: 99%